Adiantum capillus-veneris Linn (Maidenhair fern) Reported by Ibn Rushd. Traditional Used and Modern Application: A Review Article - Arwa Al-Khatib; Suleiman Olimat (Pharmaceutical Research: Recent Advances and Trends Vol. 9, 2024)
Adiantum capillus-veneris Linn (Maidenhair fern) is an herb belonging to the family Pteridaceae. Ancient physicians mainly administrated the fronds of Maidenhair fern as a single medicine or in combination with other plants in multi-herbal formulations for curing different diseases. Ancient practitioners generally used fronds of Maidenhair fern as the most useful part of the herb This is a specific review of Adiantum capillus-veneris L. (adianthum), known as Barshawshan, and Kuzburat-el bir in Arabic, focusing in the current ethnopharmacological research confirming the mention of the use by Ibn Rushd, such as alopecia and its relation with castor oil and pumpkin, in addition to its application for the treatment of skin disorders. Some of the confirmed pharmacological effects in modern medicine including anticonvulsant, antispasmodic, diuretic, antilithiatic, anti-hair loss, anti-inflammatory, and analgesic effects were declared by ancient physicians as well. Many fern species are used in traditional medicine by indigenous communities and described in folklore and some have been accepted as main sources of drug discovery.